MENINGKATKAN MOTORIK HALUS ANAK USIA 5-6 TAHUN MELALUI KEGIATAN ECOPRINT DI PAUD ASSALAFIYAH BANYUSARI - Zuhriyah, Zuhriyah; Novianti Yusuf, Rini; Supriatna, Asep (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The low level of fine motor skills of children in group B.2 at PAUD Assalafiyah Banyusari. This situation is evident from their inability to draw and colour, cut according to patterns, lack of creativity, lack of focus, and lack of accuracy in doing assignments so that, their level of fine motor achiement is 30% and is in the category of not yet developed. This study aims to improve the fine motor skills of children in group B.2 at PAUD Assalafiyah Banyusari through ecoprint activities. Classroom action research is the method used in the study, following the Kemmis and McTaggart model which includes two cycles. Each cycle includes the stages of planning, implementation of actions, observation, and reflection. Data were collected through direct observation, documentation of student ctivities, and interviews with teachers. Data were analyzedusing qualitative descriptive analysis. The initial results of the study stated that their fine motor skills were at 30%, but after the action in cycle ll, the skills increased by 50%, then in the cycle ll by 70%. The results of the study showed that ecoprint activitiescan improve children’s fine motor skills, which are characterizedby an increase in children’s abilities in carrying out activities that require hand-eye coordination, controlling hand movements while holding ecoprint equipments, and responding to patterns and shapes. Therefore, this study concluded that ecoprint activities can be an alternative to improve the fine motor skillsof children in group B.2 at PAUD Assalafiyah Banyusari.